The internet-based model of higher distance education-a case of the Warsaw University of Technology / Izabela Maleńczyk - Maleńczyk, Izabela (Research Management Centre (RMC), 2020)
In the Polish academic environment, many activities have been devoted to improve and enrich didactics. Many of them are based on the implementation of modern technologies and the Internet into various forms of academic education. The paper analyses legal framework, potential and barriers related to e-learning in Polish institutions of tertiary education. The aim of the article is to present the organisational structure, the model of functioning and management and the types of courses offered by the Centre for Open and Distance Education at Warsaw University of Technology (CODE WUT). The role of CODE WUT in shaping the culture within the organisation and its implementation in the academic world has been described. This was followed by a description of an academic multimedia textbook model and its role in the educational process. The article also attempts to define the basic business processes and analyses their structure using the BPMN notation. Finally, students' opinion on e-learning significance and their evaluation of effectiveness and satisfaction of online classes were empirically surveyed and discussed.